Application of projective infrared angiography in venipuncture for a patient with myelodysplastic syndrome (投影式红外血管成像仪在1例骨髓增生异常综合征患者静脉穿刺中的应用) - BAI Yu (白羽); SUN Jingwen (孙静雯) (Association of Integrative Nursing, 2021)
This paper summarized the application experience of projective infrared angiography in venipuncture for a patients with myelodysplastic syndrome(MDS). Venipuncture guided by projective infrared angiography can not only improve the success rate of venipuncture, reduce the time of venous catheterization, but also improve the satisfaction of patients. (本文总结1例骨髓增生异常综合征患者静脉穿刺中运用投影式红外血管成像仪辅助穿刺的经验。投影式红外血管成像仪引导下进行静脉穿刺, 能够提高静脉穿刺成功率, 缩短静脉置管时间, 提高患者满意度。)